(untitled) (Research, Society and Development, 2020)
This research aimed to analyze the speeches that have a real effect that were released by the Ministry of Education (MEC) and the Federal Government materialized in government advertisements on the MEC channel on YouTube. In this channel, the corpus was selected to carry out this research, the government advertisement entitled “With the New High School you can decide your Future!” To theoretically base this research, it was based on the studies of Michel Foucault (1995, 2014, 2018). The question that guided this study was: What was the discourse with the real effects of macropoweres was reproduced in the speeches of the micropowers materialized in the advertisement “with the New High School you can decide your Future” for the subjection of the bodies. After the analysis, the following speeches were found to circulate as if they were true: (1) the change in the organization related to high school is promising for the future of students. (2) Students who choose the Technical and Professional Training formative itinerary, upon completing their education, will have an immediate place in the job market. (3) The student will be able to choose the areas of knowledge of his interest and, thus, decide on his own future. (4) the restructuring of secondary education took place in moments of good vibes, positive thoughts and favorable political and social situations to meet the educational desires of young Brazilians. After the investigation, it was reflected that accepting governmental discourse with truth effect as if the discourse were the truth itself is naive, since it is necessary to question the discourses that are transmitted by the media.